On the domain of analytic continuation of Lauricella–Saran’s hypergeometric functions $F_M$ and their ratios - Dmytryshyn, R.; Nyzhnyk, I.; Дмитришин, Роман; Дмитришин, Роман; Нижник, Іван (Institute of Mathematics, NAS of Ukraine, 2026)
UDC 517.5 We consider the problem of extending the Lauricella-Saran's hypergeometric functions $F_M$ by branched continued fractions. In three-dimensional complex space, the domain of analytical continuation of the Lauricella-Saran's hypergeometric functions $F_M$ and their ratios is established.